1999
DOI: 10.1074/jbc.274.39.27734
|View full text |Cite
|
Sign up to set email alerts
|

TM20, a Gene Coding for a New Class of Transmembrane Proteins Expressed in the Meristematic Tissues of Maize

Abstract: In the course of the analysis of lachrima, a recessive, defective kernel, embryo-lethal mutation in Zea mays that alters embryo and endosperm development, a gene coding for a new class of transmembrane proteins was isolated. The mutant was produced by Ac transposon tagging, and a gene located in the insertion region of the transposon was isolated as well as the corresponding cDNA. The predicted protein contains twenty hydrophobic segments that can be grouped in five repeats formed by four segments that fulfill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 24 publications
6
28
0
Order By: Relevance
“…In the genome of Arabidopsis, despite their large number, PCMP genes are rarely clustered in tandems and therefore, recombination events between recently (not too divergent) duplicate motifs, either in the same gene or in recently reverse transcribed genes, have been probably lessened. One of the most attractive hypotheses for PCMP block duplication is the involvement of local microrecombinations as previously suggested for the formation of a gene coding for a maize (Zea mays) membrane protein, TM20, made of 20 hydrophobic domains that can be grouped in five homologous classes of four domains (Stiefel et al, 1999). For PCMPs as for membrane polypeptides, physicochemical properties or secondary structures are the direct object of selection rather than the amino acid sequence stricto sensu and, even in the exceptionally favorable case of TM20, the sequence divergence between different repeats largely obscured the evolutionary relationships between them.…”
Section: Resultsmentioning
confidence: 99%
“…In the genome of Arabidopsis, despite their large number, PCMP genes are rarely clustered in tandems and therefore, recombination events between recently (not too divergent) duplicate motifs, either in the same gene or in recently reverse transcribed genes, have been probably lessened. One of the most attractive hypotheses for PCMP block duplication is the involvement of local microrecombinations as previously suggested for the formation of a gene coding for a maize (Zea mays) membrane protein, TM20, made of 20 hydrophobic domains that can be grouped in five homologous classes of four domains (Stiefel et al, 1999). For PCMPs as for membrane polypeptides, physicochemical properties or secondary structures are the direct object of selection rather than the amino acid sequence stricto sensu and, even in the exceptionally favorable case of TM20, the sequence divergence between different repeats largely obscured the evolutionary relationships between them.…”
Section: Resultsmentioning
confidence: 99%
“…The characterization of empty pericarp (emp) mutants showed that loss of the negative regulator of the heat shock response Emp2 (Fu et al, 2002) or the mitochondriontargeted pentatricopeptide repeat protein Emp4 (Gutierrez-Marcos et al, 2007) affects both embryo and endosperm development. Lesions in the Cys proteinase Dek1 (Lid et al, 2002) cause a defective kernel (dek) phenotype similar to the one observed after loss of the transmembrane protein Lachrima (Stiefel et al, 1999). Finally, the analysis of etched (et) mutants indicated that the zinc ribbon protein Etched1 (da Costa e Silva et al, 2004) is needed to avoid fissures and cracks in the maize kernel.…”
mentioning
confidence: 99%
“…Homologues of TaTM20 exist in Oryza sativa and Z. mays (30,44), but not in Arabidopsis, which indicates that this family of proteins is unique to monocotyledonous plants. Ectopic expression of TaTM20 in Arabidopsis had little effect on the tolerance to Cd(II) or accumulation of Cd(II) (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Only one protein of the TM20 family, ZmTM20 in Z. mays, has been characterized to date. ZmTM20 is expressed during embryogenesis (30) and was shown to transport auxin when expressed in Xenopus oocytes (44). However, transport of auxin by ZmTM20 has not been demonstrated in planta.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation